Immigration, Labor Markets and Discrimination : Evidence from the Venezuelan Exodus in Peru - Groeger, Andre; León-Ciliotta, Gianmarco; Stillman, Steven (World Bank, Washington, DC, 2022)
Venezuela is currently experiencing the biggest crisis in its recent history. This has led to a large increase in emigration. According to recent estimates, there are a total of 5.6 million Venezuelan immigrants worldwide with over one million now living in Peru, which has led to an over 2 percent increase in the country’s population. Unlike in many other episodes of refugee migration, Venezuelan immigrants are not only very similar in cultural terms, but are, on average, also more skilled than Peruvians. This study first examines Venezuelans’ perceptions about being discriminated against in Peru. Using an instrumental variable strategy, the results document a causal relationship between the level of employment in the informal sector – where most immigrants are employed – and reports of discrimination. The second part is focused on studying the impact of Venezuelan migration on local’s labor market outcomes, reported crime rates and attitudes using a variety of data sources. The results provide evidence that inflows of Venezuelans to particular locations in Peru lead to better labor market outcomes for locals, decreased reported crime, as well as improved reported quality of local services, greater trust in neighbors and higher community quality.